Pharmacokinetics of a combined oral contraceptive in obese and normal-weight women - Westhoff, Carolyn L.; Torgal, Anupama H.; Mayeda, Elizabeth R.; Pike, Malcolm C.; Stanczyk, Frank Z. (Contraception (Stoneham), 2010)
This study was conducted to compare oral contraceptive (OC) pharmacokinetics (PK) in normal-weight [body mass index (BMI) 19.0–24.9] and obese (BMI 30.0–39.9) women. During the third week of the third cycle of OC use, we admitted 15 normal-weight and 15 obese women for collection of 12 venous specimens over 24 h. Using radioimmunoassay techniques, we measured levels of ethinyl estradiol (EE) and levonorgestrel (LNG). During the same cycle, women underwent twice-weekly sonography to assess ovarian follicular development and blood draws to measure endogenous estradiol (E2) and progesterone levels. Obese women had a lower area under the curve (AUC; 1077.2 vs. 1413.7 pg⁎h/mL) and lower maximum values (85.7 vs. 129.5 pg/mL) for EE than normal-weight women (p=.04 and <0.01, respectively); EE trough levels were similar between BMI groups. The similar, but smaller, differences in their LNG levels for AUC and maximum values (Cmax) were not statistically significant. While peak values differed somewhat, the LNG trough levels were similar for obese and normal-weight women (2.6 and 2.5 ng/mL, respectively). Women with greater EE AUC had smaller follicular diameters (p=.05) and lower E2 levels (p=.04). While follicular diameters tended to be larger among obese women, these differences were not statistically significant. OC hormone peak levels are lower among obese women compared to normal-weight women, but their trough levels are similar. In this small study, the observed PK differences did not translate into more ovarian follicular activity among obese OC users.